2021
DOI: 10.1177/15579883211063322
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of 5-Year Web Analytics for HeadsUpGuys: A Men’s Depression E-Mental Health Resource

Abstract: The present study reports an evaluation of web analytics, over a 5-year period, for HeadsUpGuys.org , an eHealth resource for men with depression. Google Analytics, Search Console, and Tag Manager were used to monitor user activity over the course of the website’s first 5 years (June 15, 2015–June 15, 2020). Through this period, HeadsUpGuys had a total of 1,665,356 unique users, amounting to 1,948,481 sessions and 3,328,258 page views. Organic traffic accounted for the highest proportion (53.44%; n = 1,041,277… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Participants in the current study rallied (and relied on) emotional support from friends and family, purposefully extended new psychosocial resources for objective help, and/or engaged professional care. Men’s widespread use of self-help relationship books affirms previous findings (Doss et al, 2009) and their uptake of peer and community-based group programs, e-relationship, and mental health resources (Entwistle et al, 2021; Ogrodniczuk et al, 2021; Oliffe et al, 2020) underscores the expansive nature of men’s help beyond the predominance of professional mental health care services. Pre-COVID-19 work by Best and colleagues (2016) indicated that young men’s mental health help-seeking relied on connecting with trusted friends online and offline, and these pathways facilitated emotional disclosure, while formal online help was accessed and deeply valued for its anonymity, confidentiality and content.…”
Section: Discussionsupporting
confidence: 59%
“…Participants in the current study rallied (and relied on) emotional support from friends and family, purposefully extended new psychosocial resources for objective help, and/or engaged professional care. Men’s widespread use of self-help relationship books affirms previous findings (Doss et al, 2009) and their uptake of peer and community-based group programs, e-relationship, and mental health resources (Entwistle et al, 2021; Ogrodniczuk et al, 2021; Oliffe et al, 2020) underscores the expansive nature of men’s help beyond the predominance of professional mental health care services. Pre-COVID-19 work by Best and colleagues (2016) indicated that young men’s mental health help-seeking relied on connecting with trusted friends online and offline, and these pathways facilitated emotional disclosure, while formal online help was accessed and deeply valued for its anonymity, confidentiality and content.…”
Section: Discussionsupporting
confidence: 59%
“…The most visited section was the home page [ 22 ], followed by the Coping with Stress and Anxiety [ 37 ] section, which shares different coping ideas and strategies, and includes various self-assessment tests that help users understand/determine the stress levels and anxiety they are experiencing, such as the PSS and GAD-7. Other studies have similar findings that the home page was viewed most frequently [ 41 , 42 ], with the second being a “self-check page, on which users could complete a depression screening tool” [ 41 ].…”
Section: Discussionmentioning
confidence: 84%
“…Data were provided by 434 Canadian men who participated in a cross-sectional survey at the beginning of the COVID-19 pandemic: April 1 through May 30, 2020. Participants were recruited online via the HeadsUpGuys website ( https://headsupguys.org ), a leading global resource providing tips, tools, information about professional services, and recovery stories to help men fight depression and prevent suicide ( Ogrodniczuk, Beharry, et al, 2021 ). Men who expressed an interest in participating were taken to an independent survey site, which was hosted by Qualtrics, where they were presented with the informed consent page.…”
Section: Methodsmentioning
confidence: 99%